Dire Straits: How tourists on the Diamond Princess cruise endured the COVID-19 crisis - Chen, Yang; Zhang, Zihao; Wang, Tao (Tourism management (1982), 2022)
Despite insights about tourists' health risk perception, crisis management literature still lacks understanding of how tourists actually experience ongoing crises and how their in situ perception evolves. Drawing on the unique case of the quarantine of the Diamond Princess at the Port of Yokohama in early February 2020, this study investigates how tourists intuitively and affectively enact the scene of a crisis in their concurrent discourses. A unique dataset covering 2259 social media entries by tourists during the quarantine were compiled manually and examined. Tourists' concerns and emotions demonstrate two salient characteristics of the enactment of the crisis scene: expressing cautious optimism and crafting realistic lifestyle. Findings demonstrate the resilience of tourists under extreme circumstances, elucidate similarities and differences of tourists' experience mediated by language, and show their supportive attitude toward tourist industry players. Service providers can strategically use of tourists’ sensemaking and psychological resilience to improve market images.